Controlled biocatalytic synthesis of a metal nanoparticle-enzyme hybrid: demonstration for catalytic H2-driven NADH recycling - Browne, LBF; Sudmeier, T; Landis, MA; Allen, CS; Vincent, KA (Wiley, 2024)
Here we demonstrate the preparation of enzyme-metal biohybrids of NAD+ reductase with biocatalytically-synthesised small gold nanoparticles (NPs, <10 nm) and core-shell gold-platinum NPs for tandem catalysis. Despite the variety of methods available for NP synthesis, there remains a need for more sustainable strategies which also give precise control over the shape and size of the metal NPs for applications in catalysis, biomedical devices, and electronics. We demonstrate facile biosynthesis of spherical, highly uniform, gold NPs under mild conditions using an isolated enzyme moiety, an NAD+ reductase, to reduce metal salts while oxidising a nicotinamide-containing cofactor. By subsequently introducing platinum salts, we show that core-shell Au@Pt NPs can then be formed. Catalytic function of these enzyme-Au@Pt NP hybrids was demonstrated for H2-driven NADH recycling to support enantioselective ketone reduction by an NADH-dependent alcohol dehydrogenase.